Importance, Nutrient content and Factors Affecting Nutrient content of Potato - Tolessa, Egata Shunka (Academy of Agriculture Journal, 2018)
Potato(Solarium tuberosum) are a source of both food and income in the growing countries of the world which can change greatly the food security ensuring capacity of countries as result of high productivity per unit area and time in relation to other crops. In addition, high prospects for growth of the market for fresh potatoes (Scott et al. 2000); make the commodity fundamental for rural development particularly in countries where there is dramatically increase in cereal purchase costs.